2012
DOI: 10.1590/s0100-69162012000500006
|View full text |Cite
|
Sign up to set email alerts
|

Utilização do farelo de conchas de vôngole na adsorção de fósforo e como corretivo da acidez do solo

Abstract: RESUMO:Teve-se o objetivo de, com a realização deste trabalho, obter a curva de neutralização do pH de amostras dos horizontes A e B de um Latossolo Vermelho-Amarelo distrófico, utilizandose de farelo de conchas de vôngole (Anomalocardia brasiliana); além disso, avaliar a capacidade de adsorção de fósforo, obtendo-se a isoterma de adsorção de melhor ajuste aos dados obtidos. Verificou-se que o farelo de concha de vôngole apresenta potencial para uso como corretivo de acidez do solo e que a dose recomendada par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The high neutralizing power of the alternative products in the present study gives them a high TRNP value, which characterizes them as being suitable for use as water acidity correctors. The TRNP of oyster shells and Venus clam shell powders observed in the present study were similar to those found by Lo Monaco et al (2012) for the shells of A. flexuosa (95.4%) and were superior to that of the shells of C. rhizophorae (86.5%) (Lo Monaco et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The high neutralizing power of the alternative products in the present study gives them a high TRNP value, which characterizes them as being suitable for use as water acidity correctors. The TRNP of oyster shells and Venus clam shell powders observed in the present study were similar to those found by Lo Monaco et al (2012) for the shells of A. flexuosa (95.4%) and were superior to that of the shells of C. rhizophorae (86.5%) (Lo Monaco et al 2015).…”
Section: Discussionsupporting
confidence: 89%